Experiences of Women Elite Leaders Doing Gender: Intra‐gender Micro‐violence between Women. (15th May 2014) - Mavin, Sharon; Grandy, Gina; Williams, Jannine
<x xml:space="preserve">Abstract</x> This paper responds to the dearth of research into women's negative intra‐gender relations and lack of understanding as to why and how these relations manifest. Through a qualitative study of women elite leaders' experiences in UK organizations, the research considers how gendered contexts, women doing gender well and differently simultaneously, intra‐gender competition and female misogyny may explain negative intra‐gender social relations between women. We consider micro‐aggression research and women's abjection and offer a unique conceptualization of intra‐gender micro‐violence with themes of disassociating, suppression of opportunity and abject appearance. The themes illustrate how the masculine symbolic order shapes and constrains women elite leaders' social relations with other women. We conclude that raising consciousness to intra‐gender micro‐violence between women is important as a means of disruption; to facilitate women and men's acceptance of intra‐gender differences between women; and to open up opportunities and possibilities for women in organizations.